Use, tolerability, benefits and side effects of orthotic devices in Charcot-Marie-Tooth disease - Bertini, Alessandro; Manganelli, Fiore; Fabrizi, Gian Maria; Schenone, Angelo; Santoro, Lucio; Cavallaro, Tiziana; Tagliapietra, Matteo; Grandis, Marina; Previtali, Stefano Carlo; Falzone, Yuri Matteo; Allegri, Isabella; Padua, Luca; et al. (Journal of neurology, neurosurgery and psychiatry, 2024)
BackgroundShoe inserts, orthopaedic shoes, ankle-foot orthoses (AFOs) are important devices in Charcot-Marie-Tooth disease (CMT) management, but data about use, benefits and tolerance are scanty.MethodsWe administered to Italian CMT Registry patients an online ad hoc questionnaire investigating use, complications and perceived benefit/tolerability/emotional distress of shoe inserts, orthopaedic shoes, AFOs and other orthoses/aids. Patients were also asked to fill in the Quebec User Evaluation of Satisfaction with assistive Technology questionnaire, rating satisfaction with currently used AFO and related services.ResultsWe analysed answers from 266 CMT patients. Seventy per cent of subjects were prescribed lower limb orthoses, but 19% did not used them. Overall, 39% of subjects wore shoe inserts, 18% orthopaedic shoes and 23% AFOs. Frequency of abandonment was high: 24% for shoe inserts, 28% for orthopaedic shoes and 31% for AFOs. Complications were reported by 59% of patients and were more frequently related to AFOs (69%). AFO users experienced greater emotional distress and reduced tolerability as compared with shoe inserts (p<0.001) and orthopaedic shoes (p=0.003 and p=0.045, respectively). Disease severity, degree of foot weakness, customisation and timing for customisation were determinant factors in AFOs’ tolerability. Quality of professional and follow-up services were perceived issues.ConclusionsThe majority of CMT patients is prescribed shoe inserts, orthopaedic shoes and/or AFOs. Although perceived benefits and tolerability are rather good, there is a high rate of complications, potentially inappropriate prescriptions and considerable emotional distress, which reduce the use of AFOs. A rational, patient-oriented and multidisciplinary approach to orthoses prescription must be encouraged.